Coping with the Life Expectancy Gap: Amending the Retirement Age to Restore Actuarial Neutrality Across Generations - Bravo, Jorge Miguel (2020)
Bravo, J. M., Ayuso, M., Holzmann, R., & Palmer, E. (2020). Coping with the Life Expectancy Gap: Amending the Retirement Age to Restore Actuarial Neutrality Across Generations. In C. H. Skiadas (Ed.), Book of Abstracts of the 6 th Stochastic Modeling Techniques and Data Analysis International Conference with Demographics Workshop : 2-5 June, 2020 ISAST: International Society for the Advancement of Science and Technology.